ICT development : economy, politics and inequality in Malaysia / Abd. Rasid Abd. Rahman - Abd. Rahman, Abd. Rasid (Universiti Teknologi MARA, Shah Alam, 2009)
Since independence in 1957, Malaysia has been profoundly transformed economically, socially and politically. Essentially premised on its various development strategies and programmes, the successful story of the Malaysian economy can be attributed to its market-oriented policies with regard to private sector investment and activities, both domestic and foreign. With the emphasis targeted at achieving long-term sustainable growth in equity, the basic philosophy of growth since 1970s, should be accompanied by improvements in the distribution of income and social stratification. Goals are not only set in economic terms but also in the form of social targets such as those envisaged in the New Economic Policy (NEP), New Development Policy (NDP) and initially in the current Vision 2020. But with the increasing engagement in the liberalisation process and ICTs, as in its recent economic policy for instance, the question of how well this can be the basis of its future attainment is something that is interesting to investigate. This question is based on the argument made by many that the continuous engagement in such developments will further divide the society (Castells, 2000a, 2000b, 2004; Norris, 2001).